Relatório de estágio curricular supervisionado em medicina veterinária: áreas de clínica, cirurgia e manejo de animais silvestres - (:unkn) unknown (Universidade Federal do Pampa, 2015)
This report describes the activities monitored and/or developed during the Supervised Curricular Internship in Veterinary Medicine (ECSMV). This internship was carried out in the areas of clinical practice, surgery and handling of wild animals at the veterinary hospital of the Federal University of Paraná, located in the city of Palotina - PR, under the supervision of Veterinarian Professor Anderson Luiz de Carvalho and academic guidance of Veterinarian Professor Roberto Thiesen. The internship was carried out from September 8, 2014 to December 19, 2014, totaling 600 hours. During this period, it was possible to monitor and assist in the activities of the resident veterinarians of the veterinary hospital, such as consultations and hospitalizations, in addition to monitoring and assisting in the practical classes of the discipline of Clinical Medicine and Surgery of Wild Animals, taught by Professor Anderson Luiz de Carvalho, held at the Veterinary Hospital or at the Municipal Zoo of Cascavel - PR, which has an agreement with the Federal University of Paraná. Through these activities, it was possible to monitor the handling of various species of birds, reptiles and wild mammals, the treatment for different illnesses in the clinic and surgery and the physical and chemical containment of these animals
Supervised internship report in veterinary medicine: clinical, surgical and wild animal management areas
Keywords: Clinica veterinária; Animais silvestres; Medicina veterinária; Veterinary Medicine; Cirurgia de animais; Animal surgery; Wild animals; Veterinary clinic; CNPQ::CIENCIAS AGRARIAS